Model Pembelajaran Active Learning Dengan Strategi Pengajuan Pertanyaan untuk Meningkatkan Kualitas Proses Pembelajaran PKn - Dodik Kariadi; Wasis Suprapto (Universitas Hamzanwadi, 2018)
Based on the research done, in the acquisition of active learning with the strategy of asking questions as the most appropriate learning model to be used on the Civic subjects in school. The purpose of this model is for students to be able to think and think critically. In this study, the author uses descriptive-critical research with more emphasis on the power of analysis of existing sources and data by relying on existing theories and concepts to be interpreted based on the writings that lead to the discussion. The results showed that students 'confidence, teachers are more open to students, The existence of healthy competition among students in the classroom, Increasing the enthusiasm and seriousness of students, Reducing the knowledge gap between students, The students' learning spirit outside school is increasing, like the whole subjects, The emergence of creative ideas from both students and teachers in order to advance the quality of education in each school, and Increase synergy and cohesiveness between students and inter-teachers. Thus, to realize innovative learning, it can be used because